Nile tilapia (Oreochromis niloticus) challenged infection by Francisella noatunensis subsp. orientalis via an intragastric route protocol - Fernandez-Alarcon, M. F.; Santana, A. M.; Viadanna, P. H.O.; Manzini, B.; Natori, M. M.; Ishikawa, C. M.; Dias, D. C.; Ranzani-Paiva, M. J.T.; Squassoni, G. H.; Couto, F. D.; Furlan, L. R. [UNESP]; Tachibana, L. (Elsevier, 2019)
Francisella noatunensis subsp. orientalis (Fno) is an emerging bacterial pathogen that causes acute or chronic disease in tilapia (Oreochromis sp). Previous studies have established experimental models of Fno infection via intraperitoneal and immersion route. However, there have been no reports of Fno challenge through the gastrointestinal mucosa. In this study, we aimed to determine the median lethal dose (LD50) of Fno by intragastric infection, evaluating the clinical signs, mortality, anatomopathological findings, and recovery of pathogenic bacteria from infected organs of infected tilapia. A total of 200 tilapias, weighing approximately 20 g each, were equally distributed in 20 aquariums, containing 50 L of water maintained at 23 °C; five different randomized treatments, were applied to them. Tilapias were either inoculated (via an intragastric injection) with 300 μL of saline solution (CON) or bacterial solution containing 3.99 × 106 CFU (INF 106), 3.99 × 105 CFU (INF 105), 3.99 × 104 CFU (INF 104) and 3.99 × 103 CFU (INF 103) of Fno. Tilapias were monitored for up to 15 days postinfection (dpi) and mortality rates recorded to calculate the LD50. At 15 dpi, necropsies and microbiological analyses were performed in the surviving fish from all groups. In addition, histopathological evaluations (spleen, gill, intestine, liver, kidney, and brain) and Fno confirmation assays were performed in CON and INF 105 (mortality closer to LD50) inoculated tilapias. While no mortality was observed in CON, mortality rates ranged from 42.5 to 80.0% in the Fno inoculated groups. Both microbiological and PCR analyses confirmed the presence of Fno in the internal tissues (kidneys and spleen) of the INF 105 group. Fno challenged groups showed macroscopic lesions in several tissues, which were consistent with the pathological features of francisellosis. Additionally, INF 105 group had microscopic lesions suggestive of the disease. This study determined the LD50 of Fno by the intragastric infection methodology, after 15 dpi, at 6.32 × 104 CFU. We report for the first time that Fno inoculated through the intragastric route, can reach the internal organs of tilapia, causing lesions in spleen, liver, and kidneys. This finding is important to test the efficacy of substances targeting the intestinal mucosa, such as prebiotics, probiotics, and organic acids. Moreover, the intragastric challenge for Fno presented here may be useful to improve the comprehension of the physiopathology of the disease.
Keywords: Disease; Experimental challenge; Francisella; Gastrointestinal tract and Tilapia